Asociación entre deterioro del flujo espiratorio máximo y prevalencia de enfermedades cardiovasculares y metabólicas en población adulta chilena: hallazgos preliminares de la Cohorte del Maule (MAUCO) - Orena Ch, Viviana; Valdivia C, Gonzalo; Ferreccio R, Catterina (Revista Chilena de Enfermedades Respiratorias, 2019)
Introduction: Chronic respiratory diseases determine high morbimortality and cardiometabolic comorbidities. We evaluated the association between peak expiratory flow (PEF) and cardiometabolic conditions in adults in a semi-rural area, in the baseline of MAUCO cohort (MAUle COhort). Material and Method: Cross-sectional study (3,465 adults, 40-74 years). Peak expiratory flow (PEF) (mini-Wright, ATS standard) was measured (Gregg & Nunn; impaired PEF ? 80% predicted). Self-reported/measured hypertension (HT), cerebrovascular disease (CVD), myocardial infarction (AMI), diabetes mellitus 2 (DM2), blood pressure, glycemia, cholesterol, weight and height were obtained. Physical activityand smoking were surveyed, after Ethical approval. Association`s measures, prevalence and Odds Ratio (OR) were calculated. Results: Sample of 63.9% of women, mean age 55 (± 9) years, schooling 9 (± 4) years. 84.7% had overweight, 81.5% physical inactivity 29.4% smokers. Low PEF: 50.6% (48.9-52.3). Self-reported was: CVD 2.2% AMI 3.3%, suspicion of hypertension 24% and DM2 2.7%. Crude OR`s were significant for women by self-reported hypertension, stroke, AMI and self-reported/suspicion DM2; in men for self-reported CVD, suspected DM2 and self-reported/suspected hypertension. The association remained post-adjusted in women self-reported AMI -moderate deterioration (OR = 2.49) and severe PEF (OR = 2.60) and in men suspected DM2 and mild (OR = 5.24) and severe deteriorated PEF (OR = 6.19). Conclusions: PEF was significantly associated with cardiometabolic diseases; sexspecific findings for AMI (women) and suspicion of DM2 (men). High prevalence of altered PEF and chronic cardiometabolic diseases were detected among the studied population.